2010
DOI: 10.1177/1352458510381257
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of motor skill learning in patients with multiple sclerosis

Abstract: Background-Several studies have demonstrated benefits of rehabilitation in multiple sclerosis (MS). However, the neuroscientific foundations for rehabilitation in MS are poorly established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 51 publications
10
84
1
Order By: Relevance
“…However, the improvement observed was significantly lower than in the control group. This finding is in agreement with the results of Tomassini et al (31) and Stoquart-Elsankari (35) indicating that motor skill learning is partially preserved in MS patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, the improvement observed was significantly lower than in the control group. This finding is in agreement with the results of Tomassini et al (31) and Stoquart-Elsankari (35) indicating that motor skill learning is partially preserved in MS patients.…”
Section: Discussionsupporting
confidence: 83%
“…This explanation could have direct implications for instructional techniques in applied settings (23). Studies in MS patients suggest that the ability of MS patients to learn motor skills is partially preserved (30)(31). However, the impact of EI on implicit learning in this population has not been considered in any studies.…”
Section: Introductionmentioning
confidence: 99%
“…Tomassini et al pointed out different results, showing that the potential to learn a new motor skill is preserved in MS patients across a wide range of disability, as even most severely damaged patients were capable of performance improvements of similar magnitude to those seen in controls [59].…”
Section: Pappalardo Et Al Mult Scler and Demyelinating Dismentioning
confidence: 99%
“…21 Another study showed that neuroplasticity in MS can be improved nearly to the same level as healthy controls when individuals are given repeated isometric visuomotor tracking tasks to perform. 9,20 With task practice, patients showed decreasing tracking errors and decreased areas of brain oxygenation, as shown by functional magnetic resonance imaging (fMRI). However, other investigations show that patients with primary progressive MS had impaired or absent brain neuroplasticity compared with those with relapsing-remitting MS (RRMS).…”
Section: The Importance Of Neuroplasticity In Multiple Sclerosismentioning
confidence: 99%
“…8 This affects the ability of the brain to recover during neurological disease or after injury. 9 von Monakow believed that neurons in contact with or surrounding damaged brain areas, suddenly function abnormally or cease to function. This proposal was highly prescient and was confirmed by imaging and electrophysiological studies almost a century later.…”
Section: The Importance Of Neuroplasticity In Multiple Sclerosismentioning
confidence: 99%